Self sufficiency trends in the food production of northern province A spatial analysis - Subajini, U. (University of Jaffna, 2011)
Northern Province, comprising five administrative districts has agriculture as its main economic activity. The province is itself endowed with sufficient internal facilities for the development of agriculture. Paddy cultivation stands foremost among the food production activities of the province, where the staple food of the people is rice. Two decades ago, records reveal that this province produced more than 30% of the Island's total production of paddy. This was in excess of the actual requirements of the province. To the contrary, in recent times, rice production is drastically dropping down to such low levels that local production has become hardly sufficient to meet even domestic requirement. The total rice requirement for an area cannot be decided on the basis of any available population statistics alone. There are other factor such as age and sex which play a dominant role in assessing the total requirement of the people in that area. Hence, whether the production of paddy is in excess or deficit to meet the requirements of the population it can be assessed correctly, only by assessing their needs on the bases of age and sex of the people of a particular area. The census and statistical department of Sri Lanka, has pointed out that according to reports of the World Agriculture Organization, the average annual rice consumption per individual is 101.45 kg. But this is only an approximate data to determine the total requirements of rice. Some districts in Northern Province produce more rice than required, while others produce less. This disparity repeats itself on a divisional basis too, whereby the production of rice in certain divisions is in excess while shortages prevail in others. The need for rice requirement varies according to sex and age of the people. Thus this study aims at analyzing the trends of self sufficiency at Divisional levels, comparing production with the demand for rice, based on sex and age of the people. This analysis is made, using only some secondary data. These data have been obtained from the statistical files of the respective divisional secretariats for the year 2010 on the basis of male, female and age. The data on rice production were also obtained for the same year. In order to access the country's total rice requirements, it becomes necessary to first determine and individual's requirement of rice. In 1969, the Medical research Institution of Sri Lanka, assessed the individual's requirement on an age and sex basis. It has also released a Co-efficient of consumption in this regard. According to this, more rice is allocated to males coming within the age group 15-19. This group forms the complete consumption unit. The co-efficient of consumption here is at 1.00. Likewise, the medical research institute has calculated the role of each age group in the complete consumption unit, on a co-efficient of consumption units and thereby their total requirement of rice is determined. For example, it has been found that males of the age group 15-19 consume double the amount of rice consumed by females within the age group 20-29. A review of the period of study on rice requirement, excesses and deficit etc. would reveal the trend of the production of rice of the districts concerned as well as the requirement of rice of the people has been assessed on the bases of sex and age, we are able to obtain reliable result on the trends of rice production at the divisional, district and provincial levels. Hence, this study would be of immense value to policy makers on paddy cultivation and to plan, as well as to policy makers on the basis of divisional secretariat, and to those who are interested in planning.
Keywords: Secretarial Divisions; Sex; Age; Co-efficient of consumption; Consumption unit